Sex determination and acclimation response of dwarf snakehead fish Channa limbata from West Java - Tri Soelistyowati, Dinar; Oman Sudrajat, Agus; Arfah, Harton; Alimuddin, Alimuddin; Hafidah, Riva; Hanggara, Yudha; Edison, Thomas (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
The Channa limbata fish is a type of tropical freshwater fish of the Channidae family which is relatively small as an aquarium ornamental fish with a distinctive color at the tip of its dorsal fin and has a snake-like head (dwarf snakehead). Natural snakehead fishing activities have threatened its sustainability. Breeding C. limbata fish through cultivation can increase its potential for sustainable use. This study aims to evaluate the acclimation response of wild-type dwarf snakehead fish in captivity and its sexual characteristics as a basis for domestication and hatchery technology. The fish samples used were natural catches from rivers in West Java measuring <100 mm to >150 mm of body length then individually acclimated indoors in an aquarium (35×20×20 cm) for 14 days. Snakehead fish live in shallow, slow-flowing river waters with a temperature of 20.2-21.3°C, TDS 16-24 mg/L at neutral pH, while the rearing water temperature and TDS are higher (temperature: 24.9-27.6°C; TDS: 88-110 mg/L). The fish mortality rate during acclimation reached 25% in fish measuring >150 mm of length on tenth day, while fish measuring <150 mm more adaptive with 100% survival. The male fish measuring 100-150 mm have 13-15 pectoral fin rays while female fish have fewer (13-14). The gonad development level of male C. limbata in nature is slower than female fish measuring 100-150 mm with a gonadosomatic index of ovaries reached 10 times higher than testicular. Keywords: acclimation, C. limbata, gonadosomatic index, ovaries ABSTRAK Ikan Channa limbata merupakan jenis ikan air tawar tropis dari famili Channidae yang berukuran relatif kecil sebagai ikan hias akuarium dengan warna yang khas pada ujung sirip punggungnya dan bentuk kepala mirip ular (dwarf snakehead). Aktivitas penangkapan ikan gabus alam telah mengancam kelestariannya. Pembibitan ikan C.limbata melalui budidaya dapat meningkatkan potensi pemanfaatannya secara berkelanjutan. Penelitian ini bertujuan untuk mengevaluasi respons aklimatisasi ikan gabus alam di dalam penangkaran dan karakterisasi seksualnya sebagai landasan teknologi pembenihan ikan gabus C. limbata yang tepat. Sampel ikan yang digunakan merupakan hasil tangkapan alam dari sungai di Jawa Barat berukuran <100 mm hingga >150 mm kemudian diaklimasi indoor di akuarium (35×20×20 cm) selama 14 hari. Ikan gabus hidup di perairan sungai yang dangkal berarus lambat dengan suhu 20,2-21,3°C, TDS 16-24 mg/L dan pH netral, sedangkan suhu air pemeliharaan dan TDS lebih tinggi (suhu: 24,9-27,6°C; TDS: 88-110 mg/L). Angka kematian ikan selama aklimatisasi mencapai 25% pada ikan berukuran >150 mm hari ke 10, sedangkan ikan berukuran <150 mm lebih adaptif dengan sintasan 100%. Ikan jantan C.limbata berukuran 100-150 mm memiliki jari-jari sirip pektoral berjumlah 13-15, sedangkan ikan betina lebih sedikit (13-14). Tingkat perkembangan gonad ikan jantan lebih lambat dari pada ikan betina dengan indeks gonadosomatik ovarium mencapai 10 kali lipat lebih tinggi dibandingkan testis. Kata kunci: aklimatisasi, Channa limbata, indeks gonadosomatik, ovarium